NUMERICAL INVESTIGATION ON THE EFFECT OF BALCONY OPEN UPSTAND ON SMOKE CONTAMINATION IN ATRIUM UPPER BALCONIES - MOHAMMED MUTAFI, MOHAMMED ABDULLAH (2019)
Design of atrium shopping malls requires engineers, building designers, architects and fire engineers to incorporate life safety principles and safe design tools into the physical configuration of the atrium from the earliest schematic designs. Smoke contamination in upper balconies of shopping mall atriums may present a significant hazard to occupants by affecting evacuation and risking lives. Past research found that smoke contamination occurence depends upon different parameters which include fire compartment opening width, balcony breadth and depths of the plume at spill edge and down stand.